ANALISIS METAFORA HEWAN PADA LAGU MANDARIN TAHUN 1990-2000: KAJIAN SEMANTIK KOGNITIF - Hutapea, Farren Zefanya; Ayuningtias, Niza (Jurnal Analisis Pendidikan Sosial, 2024)
This research discusses what are the types of animals and how the meaning of animal metaphors contained in 10 mandarin songs in 1990-2000. This research uses cognitive semantic studies that study the meanings of the depiction of human nature through the use of animal names in mandarin songs in 1990-2000. To analyze the problems in this thesis, the author uses linguistic theory and cognitive semantics that analyze the concept of language in words and sentences in mandarin songs through human thought. This research aims to describe what are the types of animals and how the meaning of animal metaphors contained in 10 mandarin songs in 1990-2000. The research method used by the author is descriptive method with qualitative approach. The results obtained from this study are that there are various types of animals and various meanings contained in 10 mandarin songs in 1990-2000.